CFD modelling of a tidal stream turbine subjected to profiled flow and surface gravity waves. (September 2016) - Tatum, Sarah; Allmark, Matthew; Frost, Carwyn; O'Doherty, Daphne; Mason-Jones, Allan; O'Doherty, Tim
Abstract : Highlights: The wave–current interaction on the performance characteristics of a tidal turbine. The wave–current interaction on the loading characteristics, including the drive shaft bending moments of a tidal turbine. The frequency analysis of the loading and power data. Abstract: This study used computational fluid dynamics to investigate the effect of waves and a velocity profile on the performance of a tidal stream turbine (TST). A full scale TST was transiently modelled operating near its maximum power point, and then subjected to waves both in and out of phase with its period of rotation. A profile was then added to one of the wave models. For this set of conditions it was found that the longer period and in-phase wave had a significant effect on the power range fluctuations, with more modest variations for thrust and the average values, although this is dependent on the turbine tip speed ratio. The addition of the profile had a strong effect on the bending moment. It has been concluded that a naturally varying sea state may yield a smoothing effect in this turbine response, but that with further structural investigation it may be that some measuring and mitigation techniques are required in the event of a predominantly single long period, in-phase wave.